Avaliação dos níveis de IGF-1, glicemia e insulina em pacientes obesos mórbidos submetidos a cirurgia bariátrica - Freire, Rosimari de Faria (2006)
Individuals who are morbid may present hyperynsulinemia, dyslipidemia, arterial hypertension and insulin resistance. The axis GH/IGF-I is in change of assisting the regulation of numberless functions relates to insulin resistance and to cardiovascular risk factors associated with metabolic syndrome. The present study demonstrates the influence of bariatric surgery in the levels of the same substances in normal individuals. The (10) eutrophic individuals, who presented BMI below 25 kg/m2 as a control group, and ten (10) morbid obese individuals, that were observed during forty-five (45) days in preoperative and postoperative periods and submitted to Capella technique through videolaparoscopy. The Analysis statistics was carried through using test T of Student. Adopts a level of significance p<0, 05. It had significant difference (p= 0,0001) for the one for weight and BMC, between the group preoperative and control group, as well as between the obese individuals, when the preoperative and postoperative periods were compared. The levels of IGF-I had been lesser in group preoperative (p=0,0007) when compared with a control group. In the period of forty-days the level of IGF-I decreased still more, with a difference significant (p=0,0440) between the preoperative and postoperative obese, being the difference between this last group and the control group statistically significant (p=0,0002). The insulin level was significantly reduce when one compared the control and preoperative groups (p= 0,0167), being also significant the difference between preoperative and postoperative group (p=0,0189). It wasn t observe statistically difference in the insulin level between the control group and preoperative group (p= 0,8155). The insulin resistance was bigger for obese, with difference statistically significant between the control and preoperative (0,0190), as well as between the preoperative and postoperative groups (p=0,0340) and after forty five days didn t have more difference statistically significant between the postoperative and control groups (p=05722). Wasn t observed difference statistically significant the glycemia between the groups which were studied. It possible to conclude that bariatric surgery, over the forty-five days, induced significant reduce of body weight and BMI, a decreased of hyperynsulinemia and reduction of insulin resistance, e that the level of IGF-I in absolute values for the obese, before the surgery, was minor who the control group and reduced still more in postoperative.